ChemInform Abstract: AcOH‐Mediated Dichloroimination of Indoles Using Chloramine‐B: A Facile Access to 2, 3‐Functionalized Indolines. Issue 9 (March 2015) - Liu, Xiaozu; Hu, Qinghong; Yuan, Zeli; Liu, Peijun
Abstract Application of the described method to tryptamine (VI) affords pyrrolidinoindole (VII).